The executioners and victims in Vladimir Zazubrin’s Sliver - Karpiński, Adam (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article addresses the problem of people who were first executioners and later victims in Vladimir Zazubrin’s micro-novel Sliver. Although it was written in 1923, it wasn’t published until 1989, 52 years after the author’s death. He was arrested and then shot in 1937 in the time of terror.In Sliver, we can see the work of a checklist executioners, who mercilessly murders thousands of people, the victims of a totalitarian state. The article presents an attempt at an interpretation and analysis of Sliver, using the comparison of executioner’s and victim’s attitudes. The main character, Andrei Srubov, does his brutal work very thoroughly. However, everyday contact with his victim’s suffering and blood and the fear that arouses in him cause his madness. The executioner who has been killing class enemies of the Russian revolution becomes in the end its victim.